The Impact of Fiscal Variables on Economic Growth in Indonesia - Yesi Aprianti; Muliati Muliati; Andra Sulindrina (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2023)
Economic growth is one indicator of the government's success, and the declining economic growth rates, even at the level of districts/cities, became the strategic issue of this research. The research objective of the researcher is to analyze economic growth as a regional productivity output and address specific research problems, whether economic growth, regional income (PAD), government’s direct expenditure, balancing fund, and labor participation influence the current economic growth. The scope of the research is districts/cities in Indonesia during 2015-2020. Panel data were analyzed using General Moment Method (GMM) estimation. The results of panel data processing in 487 regencies/cities in Indonesia show that there is a significant influence between the previous year's economic growth and direct spending on economic growth. This indicates that regional economic growth in Indonesia still requires expansionary policies. Furthermore, the researcher did not find any empirical evidence of the influence of PAD growth and balancing funds on economic growth, while the labor force participation rate/TPAK shows an insignificant negative relationship to economic growth.